Analisis Perbandingan Kinerja Keuangan Bank Umum di Asean: Studi pada Indonesia, Malaysia dan Thailand - Alfi Rozikoh; Gregorius Anggana Lisiantara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this research is to determine the differences in financial performance between the Indonesian banking industry and other ASEAN countries (Malaysia and Thailand) from 2019 to 2023 using the indicators ROA, ROE, LDR, and CAR. The results of the study show that there are significant differences in the indicators of ROA, ROE, LDR, and CAR between the financial performance of Indonesian banking and the financial performance of Malaysia and Thailand.